SEGMENTASI RUANG WARNA L*a*b - Anita Sindar Sinaga (Jurnal Mantik Penusa, 2019)
Image segmentation functions to separate one object from another object. Separation is carried out based on regional boundaries which have the same form or composition. The form of light energy is worth 0 to infinity. The function of light intensity f (x, y) indicates the position of the image coordinates. Color segmentation is obtained through preprocessing conversions and transformations that produce color value values. The color of digital images results in light intensity, namely RGB, CMYK, HSV, Color Space. The colors R (Red) G (Green) and B (Blue) have a close degree of color correlation making it difficult to segment. each sample is converted from RGB - XYZ - Lab color. The average ratio of Red, Green and Blue in RGB and XYZ 1:10 colors. Segmentation uses the color L * a * b, showing the color composition of the sample data into six groups: background, yellow, magenta, purple, red and green using the grouping method. This work proposed the L*a*b color space chosen which is a homogeneous space for visual perception.